Integrated activities in STEM environment: Methodology and implementation practice. Issue 1 (26th August 2020) - Juškevičienė, Anita; Dagienė, Valentina; Dolgopolovas, Vladimiras
Abstract: Introduction: Science, Technology, Engineering, and Mathematics (STEM) and STEAM (with A for Arts) have evolved to symbolize the renewal of science education. STEAM education offers a number of benefits, such as improved problem analysis and solving skills, as well as the development of creative abilities. Many researchers reiterate the importance of STEAM‐related activities and programs, especially the integration of maker education. Despite much interest in STEAM, it is often challenging for many educators to incorporate integrated activities into their teaching practice. This paper deals with the value of STEAM integration in a methodological sense, with a focus on the maker's laboratory and physical computing, as well as the application of design thinking and computational thinking approaches. Motivation and Objectives: The goal of this study is to develop a comprehensive conceptual framework for integrated STEM curricula focusing on the following research questions: (a) how to improve daily activities of STEM education by combining the activities of different laboratories and using a design thinking approach? and (b) how to combine FabLab activities and physical computing related to teaching different aspects of computational thinking in the context of STEM? Research Methodology and Methods: As a research methodology, we implement a mixed methods strategy to combine theoretical study and empirical research based on a synthesized literature survey and the process of iterative model development based on an observational case study. We conduct a detailed case study of two applications of integrated activities based on FabLab and physical computing integration, and illustrate how design thinking can guide teachers to open up for interdisciplinary, creative, and project‐based opportunities. Results and Findings: The paper provides a conceptual framework for STEM integration activities and step‐by‐step guidelines on how design thinking methods could could interact in practice. The implications of the results may be useful for educators seeking recommendations for the integration process, which enable educators to design hands‐on activities and incorporate integrated aspect of students' STEAM learning into teaching practice. In conclusions, the authors suggest that as interdisciplinary crossroads, design thinking provides a natural bridge between subjects, and fits especially to integrate activities of the maker's labs and physical computing, focusing on the integration of computational thinking and computational making approaches within STEM education environment. The absence of a statistical evaluation, which is positioned as a further research step, may be mentioned as a limitation of the study.